Voice and Context in Eighteenth-Century Verse
XVIII, 295 p.
Keywords: This collection of essays reassesses the importance of verse as a medium in the long eighteenth century, and as an invitation for readers to explore many of the less familiar figures dealt with, alongside the received names of the standard criticism of the period.